On the analysis of temperatures, surface morphologies and tool wear in drilling CFRP/Ti6Al4V stacks under different cutting sequence strategies. (15th February 2020) - Xu, Jinyang; Li, Chao; Chen, Ming; El Mansori, Mohamed; Paulo Davim, J.
Abstract: In drilling CFRP/Ti6Al4V stacks, the cutting sequence strategy, which determines the coupling effects of each phase machining, affects significantly the machinability of the sandwiched material as well as the tool wear characteristics. The present paper contributes to a scientific understanding of the effects of different cutting sequence strategies on the drilling performance of multilayer CFRP/Ti6Al4V stacks when using uncoated tungsten carbide and diamond-coated drills. Experimental quantification of the in-situ temperatures during the stack drilling was conducted using the method of infrared thermography camera and the instrumentation of drill bits by embedded thermocouples. Drilling forces, exit burr heights of the titanium holes, surface morphologies of the composite holes and tool wear signatures were analyzed. The results indicate that drilling from titanium to CFRP leads to higher magnitudes of the composite cutting temperatures while it benefits the reduction of the stack thrust forces, the improvement of the composite surface morphologies as well as the decrease of the exit titanium burr heights. Additionally, the coupling effects of drilling temperatures and chip adhesion are the influential factors leading to the disparate effects of the cutting sequence strategy on the drill wear progression. Drilling from titanium to CFRP reduces the drill adhesion and flank wear extents owing to the brushing effects of the composite drilling. The diamond-coated drills are confirmed superior to the uncoated ones in terms of lower drilling temperatures, lower drilling forces, minimal hole surface damage, less tool wear while machining the CFRP/Ti6Al4V stacks.